A star algorithm modification for a Java knowledge based jeepney route recommender system - Wong, Bryan Inno Nueva (2009)
The large area occupied by cities, particularly Davao City, comes with complex road network that provide many routes in finding a desired destination within the city. With the Jeepney Route Recommender System, the primary mode of transportation namely jeepneys, in Davao City was taken into account. And with the overlapping routes of some jeepneys, it is important to pick one route that will give commuters the least fare since jeeepneys fare are calculated in a per kilometer basis. The Java based Jeepney Route Recommender System uses a modified algorithm, particularly the A star Algorithm. It was modified in a way that the searching becomes knowledge-based with the knowledge that (1) different road type exist ? major roads connect to minor roads in an area and (2) people prefer to travel in major roads. The system incorporated these common knowledges in finding a path between the provided source area to the preferred destination area. The system also incorporates the technology of SMS that it is able to receive input from the users via SMS and to deliver results to the users via SMS
Thesis (BS Computer Science) -- University of the Philippines Mindanao, 2009
Keywords: Star algorithm; Knowledge-based searching; Route recommender; SMS driven system